Effects and safety of Chinese herbal medicine on inflammatory biomarkers in cardiovascular diseases: A systematic review and meta-analysis of randomized controlled trials - Li, Mingdi; Zhou, Iris Wenyu; Trevillyan, Janine; Hearps, Anna C.; Zhang, Anthony Lin; Jaworowski, Anthony (Frontiers in Cardiovascular Medicine, 2022)
Inflammation drives cardiovascular disease (CVD) in individuals with underlying chronic inflammatory diseases, including People with HIV (PWH), independently of dyslipidemia. Adjunctive treatments that lower inflammation may be useful to lower CVD risk in such populations. There is very little data on the efficacy of Chinese herbal medicine (CHM) in reducing inflammation in PWH to address its potential in reducing this CVD risk factor, therefore we evaluated its impact on inflammatory biomarkers relevant to CVD risk in the general population. Six English and Chinese databases were searched for studies investigating CHM’s effects on inflammatory biomarkers relevant to CVD from respective inceptions to February 2022. A systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted and the most-frequently prescribed herbs were identified. Thirty-eight RCTs involving 4,047 participants were included. Greater than or equal to 50% of included studies had a low risk of bias in five domains (random sequence generation, detection, attrition, reporting and other bias) and 97% had a high risk of performance bias. CHM provided significant additive effects on attenuating relevant inflammatory indices including hs-CRP (SMD -2.05, 95% CI -2.55 to -1.54), IL-6 (SMD -1.14, 95% CI -1.63 to -0.66) and TNF-α levels (SMD -0.88, 95% CI -1.35 to -0.41), but no significant effects on hs-CRP were found between CHM and placebo when co-treating with Western drugs (MD 0.04, 95% CI -1.66 to 1.74). No severe adverse events were reported in CHM groups. The two most prevalent herbs present in formulae demonstrating reduction of at least one inflammatory biomarker were Dan shen (Salviae Miltiorrhizae Radix et Rhizoma) and Huang qi (Astragali Radix). CHM, in combination with standard anti-inflammatory medications, may depress inflammation and reduce the risk of inflammatory conditions such as CVD. Rigorously-conducted trials and adequate reporting are needed to provide more robust evidence supporting the use of CHM to reduce CVD risk in people with underlying chronic inflammation such as PWH.